Welfare Occupational Health Services Needs and Needs-Meeting Stratagies of University Women Academics in Benue State, Nigeria - Burbwa, Sarah Ngukuran; Kimbi, Nguamo Dinah (International Journal of Human Kinetics, Health and Education, 2022)
The study identified the Welfare Occupational Health Services Needs and needs-meeting strategies of University Women in academics, Benue State Nigeria utilizing the cross-sectional survey research design. The population of the study consisted of all women academics. Only public universities in Benue State were covered. A sample size of 288 women academics was surveyed. Adapted instruments with reliability co-efficient index of Cronbach’s Alpha .90 were used. Data were analysed using mean scores and percentages while Chi-square statistic was used to test the null hypothesis at .05 level of significance. Findings of the study indicated that Welfare Occupational Health Services Needs (WOHSNs) of women academics were transport services 62.20%, sickness benefits 79.90%, and provision of eating café 51.40%. Results further show that there were no significant differences in the WOHSNs responses of the women academics based on university type (Calχ2 value = 4.514, p = 3.094). WOHSNMS were formulated based on the identified WOHSNs. The study concludes that transport services among others are important and necessary for work efficiency and productivity. However, the WOHSNMS are essential for inclusion and implementation for women academics in the universities in Benue State.